Al-Mabadi’ Al-Islamiyah li Mu’alajati Ats-Tsaqafat Al-Mutatharrifah fi Al-Mujtama’ Al-Indunisi - Mubaraq, Zulfi; Haris, Abd; Bahruddin, Uril; Sahid, Mualimin Mochammad (el Harakah: Jurnal Budaya Islam, 2022)
لم يزل المجتمع الإندونيسي تعانيه مشكلة التطرف الديني، بل أصبحت فكرة التطرف ثقافة لدى بعض الأفراد الأكاديميين. وفي جانب آخر عرف الشعب الإندونيسي بالتسامح والتعاون والتعاطف. فأهداف البحث وصف (1) نماذج الثقافات المتطرفة في المجتمع، (2) أسباب انتشار الثقافات المتطرفة في المجتمع، (3) المبادئ الإسلامية لمعالجة الثقافات المتطرفة في المجتمع. استخدم هذا البحث المدخل الكيفي والدراسة المكتبية، وجمع البيانات فيه عن طريق دراسة الوثائق المتعلقة بالموضوع وتحليلها. ويتم بعد ذلك تنظيم البيانات وتفسيرها والمقارنة مع نتائج البحوث الأخرى ثم الاستنتاج منها. وقد توصل البحث إلى أن هناك نماذج الثقافات المتطرفة التي تتمثل في الفهم الخاطئ عن معنى والولاء والبراء والجهاد، وأن أسباب انتشار الثقافات المتطرفة نوعان الدينية التي تتمثل فيعدم فهم الدين فهما صحيحا، والأخذ بظاهر النصوص الدينية، الغلو في الدين، وضعف فهم السيرة والتاريخ، وغير الدينية تتمثل في وعد وجود العدالة في مجالات الحياة، وأن هناك مبادئ إسلاميةلمعالجتها، منها الإنكار على أهل الغلو والتقصير، وأن الوسطية من صفات الأمة، والمسامحة ولين الجانب، والرحمة والرفق والشفقة على المخالف، وإبراز الأمور المتفق عليها على المخالف، وإزالة التصورات الخاطئة وتوضيح الحقائق، وعدم الإساءة إلى الآخرين أو إلى ما يعتقدوه، وقبول الحق من المخالفين، والتركيز على القضايا الأساسية.ومن هنا يمكن أن تعمم نتائج هذا البحث بأن تطبيق المنهج الوسطيفي المجتمع الإسلامي يلزم نشر الوعي الإسلامي الوسطي ومناقشة الثقافات المتطرفة التي تؤدي إلى إساءة صورة الإسلام والمسلمين.   Indonesian people are still feared by extreme behavior, and it has even become a growing culture in the campus community. On the other hand, the Indonesian people are known to be tolerant, polite and compassionate. This study aims to uncover (1) forms of extreme culture in society, (2) factors that influence extreme culture, and (3) Islamic principles in resolving extreme culture in society. This article uses a qualitative approach to the literature study model. Data collection by means of document analysis related themes. After the data is presented in accordance with the research objectives, then it is discussed with the results of other studies, then conclusions are drawn. The findings of this study are, first: extreme forms of culture are incorrect understandings related to the meaning of al-wala’, al-bara and al-jihad, second: the reasons for the emergence of extreme culture are religious causes which are manifested by an incorrect understanding of Islam, textual understanding, excessive religious beliefs and lack of understanding of Islamic history. The non-religious causes are due to social inequality, third: Islamic principles to solve extreme cultural problems are to reject excessive religious attitudes, strengthen Islamic moderation, culture of tolerance and compassion, cooperate in agreed matters, eliminate negative stigma, refrain from hate speech, accept the truth from whomever. just and focus on the things of principle. The conclusion from the findings above shows that religious moderation will be realized because of a good and correct understanding of religion, as well as minimizing extreme cultures that damage the image of Islam.